2010
DOI: 10.1177/1938965510364931
|View full text |Cite
|
Sign up to set email alerts
|

Like It! Learn It! Use It?

Abstract: This field study examines factors influencing hotel employees’ ability to transfer the concepts that they learned in job training when they return to work. The study was conducted during a major hotel company’s training program. The training objective was to ready front-desk associates to operate a new property management system (PMS). Past business research suggests that trainee characteristics, training design, and work environment factors can positively impact an employee’s transfer of training. Role-play e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…implementing needed programs). These findings, along with those that have been presented in several related studies (Ellis et al, 2010;Frash et al, 2010;Kalargyrou and Woods, 2011;Tews and Tracey, 2009;Chew and Wong, 2008;Zhao and Namasivayam, 2009), provide a more comprehensive understanding of the factors that may influence an individual's preparation for training, performance during the learning experience and the transfer of acquired knowledge and skills back to the job. Moreover, and consistent with the implications noted above, some of these factors may be particularly relevant for hospitality organizations (e.g.…”
supporting
confidence: 59%
“…implementing needed programs). These findings, along with those that have been presented in several related studies (Ellis et al, 2010;Frash et al, 2010;Kalargyrou and Woods, 2011;Tews and Tracey, 2009;Chew and Wong, 2008;Zhao and Namasivayam, 2009), provide a more comprehensive understanding of the factors that may influence an individual's preparation for training, performance during the learning experience and the transfer of acquired knowledge and skills back to the job. Moreover, and consistent with the implications noted above, some of these factors may be particularly relevant for hospitality organizations (e.g.…”
supporting
confidence: 59%
“…Personal capacity is defined as the "extent to which individuals have the time, energy and mental space in their work lives to make changes required to transfer learning to the job" (Holton et al, 2000, p. 344). Studies using the LTSI model suggest that this construct is a significant predictor of transfer of training (Bates et al, 2007;Frash et al, 2010). This model also indicates an indirect influence on the transfer of training via motivation to transfer.…”
Section: Personal Capacitymentioning
confidence: 73%
“…The results indicated that they finally recommended practices to enhance training efficiency and raise the perceived benefits of hospitality workers. Previous business research suggested that trainee characteristics, training design, and work environment factors can positively impact an employee's training (Frash et al, 2010;Whitelaw et al, 2009). There are four levels of training effectiveness reported by Frash et al (2010) level 1, reactions, measures the trainees' liking of, and feelings for, a training program; level 2, learning, measures the principles, facts, and techniques absorbed by the trainees; level 3, behavior assesses the degree to which the learned principles and techniques are manifested in job behavior change; level 4, results, are the ends, goals, or desired business results that lead to reduction in costs or increases in production.…”
Section: Training Effectivenessmentioning
confidence: 99%